Family support to the teacher in the care of children with learning disabilities in mathematics - Bajaña Salazar, Haydeé (Ecuadorian Science Journal, 2021)
Currently, learning problems have become a critical point in basic primary and high school education. Even though in developed countries this type of problem has been investigated since the 1960s, in Latin America this topic is relatively recent. Dyslexia is the best known, but there are also disorders in mathematics, specifically dyscalculia, which is not generally known. Research indicates that most people who suffer from it are not diagnosed. Many parents are unaware that their children suffer from some type of learning problem, since many do not present obvious signs. This hinders the development of the child since early intervention has a beneficial impact on cognitive development. This work is aimed at investigating how family support affects the attention to learning problems in mathematics in fifth-year basic general education students; for this, surveys were conducted for parents, tutors, and teachers, an interview for the institution's DECE staff, and observation guides for students. A significant sample of the groups was chosen, the collected data was tabulated and analyzed, finding that there is no knowledge among most of the parents about this problem, although tutors and teachers have medium knowledge about it, and the institution has tools to help students.